Effect of using methods and norms phosphoruos fertilizer on leaf area of winter wheat - Bozorovich Khudaykulov Jonibek; Alavkhonovich Kurbonov Akhmad; Alisher Ugli Rakhimov Mirzokhid; Jahongir Khamdamov (BIO Web of Conferences)
This article presents information on the location, methods and methods of research, the effect of phosphorus fertilizers on the formation of the leaf area of winter wheat. According to this, information was provided on that before planting winter wheat seeds, using ammophos fertilizer 90 kg/ha, potash fertilizer 60 kg/ha, nitrogen fertilizer 200 kg/ha during the growing season, and apply PS-agro pure under the plow at the end of the growing season and nitrophos (NKFU) fertilizers 90 kg/ha, potassium fertilizer 60 kg/ha, compared to the options that used nitrogen fertilizer at the rate of 200 kg/ha during the growing season, the leaf area was up to 2589,7–5341,2 m2/ha, biological dry mass accumulation was up to 9,4–16,2 c/ha.